2021
DOI: 10.1186/s40662-021-00234-6
|View full text |Cite
|
Sign up to set email alerts
|

The number of intracorneal ring segments in asymmetric and central cones

Abstract: Background To compare the results of single versus double intracorneal ring segment (ICRS) (KeraRing) implantation in keratoconus with respect to different cone locations. Methods Twenty-two eyes of 18 patients with totally asymmetric cones (20–80% or 0–100% distribution along steep axis) were implanted with single ICRS (Group 1), 38 eyes of 32 patients with central or partially asymmetric cones (50–50% or 40–60% distribution along steep axis) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(57 reference statements)
0
3
0
2
Order By: Relevance
“…There are various nomograms in practice for ICRS selection considering the tomographic pattern, refractive parameters, and corneal aberrations. [ 13 14 15 16 ] In our study, group of extreme steep cornea, however, almost half of patients could not obtain refractive parameters (sphere, cylinder, and spherical equivalent) with autorefractometer, which are used to be an important basis of ring selection. The present results suggest surgical planning based on mean asphericity, despite the small sample of patients, could still achieve favorable outcomes.…”
Section: Discussionmentioning
confidence: 66%
“…There are various nomograms in practice for ICRS selection considering the tomographic pattern, refractive parameters, and corneal aberrations. [ 13 14 15 16 ] In our study, group of extreme steep cornea, however, almost half of patients could not obtain refractive parameters (sphere, cylinder, and spherical equivalent) with autorefractometer, which are used to be an important basis of ring selection. The present results suggest surgical planning based on mean asphericity, despite the small sample of patients, could still achieve favorable outcomes.…”
Section: Discussionmentioning
confidence: 66%
“…11 Canan A.et.al. 7,12 In a similar study on 42 keratoconic eyes , the UDVA and BCVA improved significantly and also found a significant reduction in refractive spherical equivalent , cylinder and SimK avg postoperatively (P<0.001). The mean postoperative Q changed from -1.06±0.48 to -0.57±0.58 (P<0.001).…”
Section: Discussionmentioning
confidence: 77%
“…The number of rings used is still controversy inspite of various nomograms present 12 .Utine et al studied the number of rings in comparison of asymmetric and central cones, there results revealed that double ring implantation were superior to single ring as regard the corneal astigmatism, keratometry, and anterior corneal asphericity for central and partially asymmetrical however single ring was superior in totally asymmetrical cones 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Intracorneal ring segments (ICRS) have long been used for visual and optical rehabilitation of ectatic corneal conditions either alone or accompanied with other treatment procedures. 1,2 In most cases it is well tolerated effective treatment with long term improvement of refractive and keratometry measurements 3 .However visual satisfaction is not guaranteed in some cases inspite of reaching close to emmetropia . 4 This visual satisfaction unpredictability is caused by the insufficiency of the lower order aberrations on which we build our choice of rings to explore the visual quality of the patients.…”
Section: Introductionmentioning
confidence: 99%